Identifying Mega-environments and Evaluating Grain Yield Stability in Bio-fortified Rice Using AMMI and GGE Approaches - Sahu, Hemant; Premi, Vinay; Bhariya, Sanjay Kumar; Mannade, Ajit Kumar; Mahant, Rahul Das (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted during July–November, 2022 in Raipur, Bilaspur, Kawardha, Mahasamund, and Jagdalpur districts of Chhattisgarh, India to identify promising rice genotypes under diverse environmental conditions. Thirty micronutrient-rich rice varieties, along with yield and micronutrient checks, were evaluated using RCBD with two replications per location. None of the candidate genotypes outperformed the standard check, Swarna, in combined mean yield performance. AMMI analysis revealed significant genotype, environment, and genotype-by-environment interactions (p<0.05). Environment 5 recorded the highest mean grain yield (6560.75 kg ha-¹), followed by E4 (5783.33 kg ha-¹) and E2 (5123.67 kg ha-¹). PCA1 and PCA2 captured 57.49% and 18.61% of genotype-environment interaction, respectively, explaining 76.10% cumulatively. Genotypes G28 and G29 demonstrated high mean yields and stability, suitable for commercial cultivation, while G19 showed high yield but lower stability, indicating potential for specific environments. Genotypes G2, G4, and G18, though low-yielding, exhibited greater stability, making them valuable for stability-focused breeding. “Which-won-where” analysis revealed G19 excelling in E5, G11 performing well in E1, E2, and E3 and G28 succeeding in E4. AMMI bi-plot showed E1 as the most informative environment for selecting widely adapted genotypes, while E3 was highly representative but less discriminative. E4 and E5 were discriminative but less representative. These findings highlight promising genotypes for the release of nutrient-rich rice varieties well-adapted to Chhattisgarh’s growing areas.